Rasio Nilai Kuat Lentur pada Beton Geopolimer dengan Penambahan Superplasticizer - Ester Surya Lie; Rachmansyah Rachmansyah (Universitas Kristen Maranatha, 2023)
Cement concrete is an alternative material in construction because it has high strength. Cement concrete has ingredients such as coarse aggregate, fine aggregate, cement and water. In produce cement have emissions such as dust particles, SO2, CO2, and other pollutants. Emissions can damage the environment so that alternatives are needed to solve them. Geopolymer concrete is concrete without cement. In this research, cement material was replaced by fly ash. This concrete is one of the environmentally friendly products because in its manufacture not using cement. In several research, the flexural strength value of geopolymer concrete has lower results compared to cement concrete. This research aims to increase the flexural strength value of geopolymer concrete so that equivalent cement concrete according to SNI 2847:2013 of 0,62√(fc'), with the addition of a 2% superplasticizer to increase the density of concrete. The beam test specimens used a size of 15 × 15 × 53 cm in total of 32 sample with mix design of geopolymer concrete using different molarities NaOH. Compressive testing and flexural testing according to SNI 1974:2011 and SNI 4431:2011. The result of this research is the flexural strength ratio of geopolymer concrete with the addition of 2% superplasticizer is 0,62√(fc'). The flexural strength ratio of geopolymer concrete equivalent to the flexural strength ratio of cement concrete in SNI 2847:2013 is 0,62√(fc').